Making Open Development Inclusive Lessons from IDRC Research - Smith, Matthew L.; Seward, Ruhiya Kristine (The MIT Press, 2020)
Drawing on ten years of empirical work and research, analyses of how open development has played out in practice. A decade ago, a significant trend in using and supporting open practices emerged in international development. "Open development" describes initiatives as wide-ranging as open government and data, open science, open education, and open innovation. The driving theory was that these types of open practices enable more inclusive processes of human development. This volume, drawing on ten years of empirical work and research, analyzes how open development has played out in practice Focusing on development practices in the Global South, the contributors assess the crucial questions of who is able to participate and benefit from open practices, and who cannot. Examining a wide range of cases, they offer a macro analysis of how open development ecosystems are governed, and evaluate the inclusiveness of a variety of applications, including creating open educational resources, collaborating in science and knowledge production, and crowdsourcing information. Matthew L. Smith is Senior Program Specialist at the International Development Research Centre in Ottawa. He is coeditor of Open Development: Networked Innovation in International Development (MIT Press and IDRC). Ruhiya Kristine Seward is Senior Program Officer at the International Development Research Centre. Contributors Denisse Albornoz, Chris Armstrong, Savita Bailur, Roxana Barrantes, Carla Bonina, Michael Cañares, Leslie Chan, Laura Czerniewicz, Jeremy de Beer, Stefano De Sabbata, Shirin Elahi, Alison Gillwald, Mark Graham, Rebecca Hillyer, Cheryl Hodgkinson-Williams, Dick Kawooya, Erika Kramer-Mbula, Paulo Matos, Caroline Ncube, Chidi Oguamanam, Angela Okune, Alejandro Posada, Nagla Rizk, Isaac Rutenberg, Tobias Schonwetter, Fabrizio Scrollini, Ruhiya Kristine Seward, Raed Sharif, Matthew Smith, William Randall Spence, Henry Trotter, François van Schalkwyk, Sonal Zavaeri